If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = (7 + -2x)(3 + -2x) Multiply (7 + -2x) * (3 + -2x) 6 = (7(3 + -2x) + -2x * (3 + -2x)) 6 = ((3 * 7 + -2x * 7) + -2x * (3 + -2x)) 6 = ((21 + -14x) + -2x * (3 + -2x)) 6 = (21 + -14x + (3 * -2x + -2x * -2x)) 6 = (21 + -14x + (-6x + 4x2)) Combine like terms: -14x + -6x = -20x 6 = (21 + -20x + 4x2) Solving 6 = 21 + -20x + 4x2 Solving for variable 'x'. Combine like terms: 6 + -21 = -15 -15 + 20x + -4x2 = 21 + -20x + 4x2 + -21 + 20x + -4x2 Reorder the terms: -15 + 20x + -4x2 = 21 + -21 + -20x + 20x + 4x2 + -4x2 Combine like terms: 21 + -21 = 0 -15 + 20x + -4x2 = 0 + -20x + 20x + 4x2 + -4x2 -15 + 20x + -4x2 = -20x + 20x + 4x2 + -4x2 Combine like terms: -20x + 20x = 0 -15 + 20x + -4x2 = 0 + 4x2 + -4x2 -15 + 20x + -4x2 = 4x2 + -4x2 Combine like terms: 4x2 + -4x2 = 0 -15 + 20x + -4x2 = 0 Begin completing the square. Divide all terms by -4 the coefficient of the squared term: Divide each side by '-4'. 3.75 + -5x + x2 = 0 Move the constant term to the right: Add '-3.75' to each side of the equation. 3.75 + -5x + -3.75 + x2 = 0 + -3.75 Reorder the terms: 3.75 + -3.75 + -5x + x2 = 0 + -3.75 Combine like terms: 3.75 + -3.75 = 0.00 0.00 + -5x + x2 = 0 + -3.75 -5x + x2 = 0 + -3.75 Combine like terms: 0 + -3.75 = -3.75 -5x + x2 = -3.75 The x term is -5x. Take half its coefficient (-2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. -5x + 6.25 + x2 = -3.75 + 6.25 Reorder the terms: 6.25 + -5x + x2 = -3.75 + 6.25 Combine like terms: -3.75 + 6.25 = 2.5 6.25 + -5x + x2 = 2.5 Factor a perfect square on the left side: (x + -2.5)(x + -2.5) = 2.5 Calculate the square root of the right side: 1.58113883 Break this problem into two subproblems by setting (x + -2.5) equal to 1.58113883 and -1.58113883.Subproblem 1
x + -2.5 = 1.58113883 Simplifying x + -2.5 = 1.58113883 Reorder the terms: -2.5 + x = 1.58113883 Solving -2.5 + x = 1.58113883 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = 1.58113883 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = 1.58113883 + 2.5 x = 1.58113883 + 2.5 Combine like terms: 1.58113883 + 2.5 = 4.08113883 x = 4.08113883 Simplifying x = 4.08113883Subproblem 2
x + -2.5 = -1.58113883 Simplifying x + -2.5 = -1.58113883 Reorder the terms: -2.5 + x = -1.58113883 Solving -2.5 + x = -1.58113883 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = -1.58113883 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = -1.58113883 + 2.5 x = -1.58113883 + 2.5 Combine like terms: -1.58113883 + 2.5 = 0.91886117 x = 0.91886117 Simplifying x = 0.91886117Solution
The solution to the problem is based on the solutions from the subproblems. x = {4.08113883, 0.91886117}
| x^2+5=16 | | 4[-8x+5]=-32x-26 | | 12-(10xn)=-28 | | -5.9a-2/3=5/6 | | -57=-19p | | -5/9-2/3=5/6 | | -6x^2=-24 | | -4x-2=-2x | | -4+4x-x=20 | | 3[1-3x]=2[-4x+7] | | 12-(10xn)=28 | | 29=n-16 | | 8-x/2=53 | | X+9+2x+6=90 | | 4x+4-x=31 | | -26=n-13 | | 1/4x+4=7 | | 3(x+3)=-3(x+1)-5 | | 2d-2+3d=38 | | -5x+18=-8x | | -2x+47=-28 | | 8x+4[4x-3]=4[6x+4]-4 | | 4/3x+2=-2 | | 7x+26=10x+8+15x | | -7x+16=x | | -5x+38=-8x+2 | | x^2+16=63 | | 6x+7y=-49 | | (x-7)/(x+6)+(x+8)/(x+1) | | 1+7x+6x=144 | | 38+7k=8[k+4] | | 5x-29=x-14-x |